Evaluation of Bio-chemical Productivity in Cyanobacterium Spirulina platensis-S5 under Heavy Metal Stress-Part II - Jetley, U.K.; Choudhary, Meenakshi; Fatma, Tasneem (Asian Journal of Chemistry, 2016)
Effect of heavy metals namely cadmium, cobalt, nickel and manganese was examined on chlorophyll, carotenoid. phycobiliprotein, carbohydrate and protein contents of Spirulina platensis-S5 in this part of the study. All the heavy metals tested in the study showed acute toxicity over a sub-lethal concentration-gradient of 0.05–0.20 mg/L with respect to chlorophyll, carotenoid and phycobiliprotein contents, the order of toxicity being Cd > Co > Ni > Mn. Carbohydrates and proteins, however, resisted heavy metal toxicity suggesting their role in metal chelation.